Progressive Pseudolithiasis Associated with the Intravenous Administration of Ceftriaxone in Patients with Central Nervous System Infections - Tsukagoshi, Setsuki (Intern Med, 2017)
We report four adult cases of ceftriaxone (CTRX)-induced pseudolithiasis and nephrolithiasis. With the exception of case 1, none of our cases showed abdominal symptoms. Our patients, who had central nervous system (CNS) infections, had been treated with CTRX (4 g/day) for 35-69 days. CTRX-induced pseudolithiasis and nephrolithiasis can appear depending on the total dose of CTRX and the duration for which it is administered. Patients with bacterial CNS infections who are treated with CTRX are typically treated with higher doses for longer periods. It should be recognized that these patients are at higher risk of developing CTRX-induced pseudolithiasis and nephrolithiasis.